CALET on the International Space Station: the first three years of observations. (29th May 2020) - Brogi, P; Adriani, O; Akaike, Y; Asano, K; Asaoka, Y; Bagliesi, M G; Berti, E; Bigongiari, G; Binns, W R; Bonechi, S; Bongi, M; Bruno, A; et al.
Abstract: The CALorimetric Electron Telescope CALET is a space instrument designed to carry out precision measurements of high energy cosmic-rays on the JEM-EF external platform on the International Space Station, where it has been collecting science data continuously since mid October 2015. In addition to its primary goal of identifying nearby sources of high-energy electrons and possible signatures of dark matter in the electron spectrum, CALET is carrying out extensive measurements of the energy spectra, relative abundances and secondary-to-primary ratios of elements from proton to iron, and even above (up to Z = 40), studying the details of galactic particle propagation and acceleration. An overview of CALET based on the data taken during the first three years of observations is presented, including a direct measurement of the electron+positron energy spectrum from 11 GeV to 4.8 TeV. The proton spectrum has been measured from 50 GeV to 10 TeV covering, for the first time with a single space-borne instrument, the whole energy interval previously investigated in separate sub-ranges by magnetic spectrometers and calorimetric instruments. Preliminary spectra of cosmic-ray nuclei are also presented, together with gamma-ray observations and searches for an e.m. counterpart of LIGO/Virgo GW events.